TOXICITY TEST OF CHANNA MICROPELTES EXTRACT BETWEEN NORMAL WISTAR RATS AND DIABETES MODEL BASED ON CARDIAC HISTOPATHOLOGY - Annisa Noviany; Amy Nindia Carabelly; Juliyatin Putri Utami (FKG Unlam, 2023)
Background: DM is metabolic disease can prolong wound healing phase and cause oxidative stress that can affect cardiac damage such as degeneration, hypertrophy, and necrosis. They can be inhibited by the effect of 16 ml/kg BW CM containing palmitic acid (18.30%), albumin (3.6147g/dl), and amino acids are leucine (1.58%) and valine (0.97%). It's proven to accelerate wound healing in normal Wistar rats and DM. However, CM extract on the cardiac is unknown, so an acute toxicity test was carried out for 14 days. Purpose: To analyze the effect of oral administration of CM extract at an effective dose of 16 ml/kg BW on the histopathological exam of degeneration, hypertrophy, and cardiac necrosis of normal Wistar rats and diabetic models. Method: This study is true experimental study with a post-test only control group design which is divided into 4 groups are 2 groups of Wistar rats normal and diabetic models who were given CM extract at an effective dose of 16 ml/kg BW, 2 groups consisted of normal Wistar rats and diabetic models which were only given BR2 feed. Results: T-Independent test and the Mann-Whitney test showed that there was a significant difference between degeneration and hypertrophy (p<0.05) and necrosis. There was no significant difference (p>0.05). Conclusion: The effective dose of CM extract 16 ml/kg BW had an effect on the cardiac of normal Wistar rats and diabetic models in the form of a decrease in the level of damage to degeneration, hypertrophy, and cardiac necrosis. Keywords: Cardiac, Channa micropeltes, Degeneration, Hypertrophy, Necrosis.Background: DM is metabolic disease can prolong wound healing phase and cause oxidative stress that can affect cardiac damage such as degeneration, hypertrophy, and necrosis. They can be inhibited by the effect of 16 ml/kg BW CM containing palmitic acid (18.30%), albumin (3.6147g/dl), and amino acids are leucine (1.58%) and valine (0.97%). It's proven to accelerate wound healing in normal Wistar rats and DM. However, CM extract on the cardiac is unknown, so an acute toxicity test was carried out for 14 days. Purpose: To analyze the effect of oral administration of CM extract at an effective dose of 16 ml/kg BW on the histopathological exam of degeneration, hypertrophy, and cardiac necrosis of normal Wistar rats and diabetic models. Method: This study is true experimental study with a post-test only control group design which is divided into 4 groups are 2 groups of Wistar rats normal and diabetic models who were given CM extract at an effective dose of 16 ml/kg BW, 2 groups consisted of normal Wistar rats and diabetic models which were only given BR2 feed. Results: T-Independent test and the Mann-Whitney test showed that there was a significant difference between degeneration and hypertrophy (p<0.05) and necrosis. There was no significant difference (p>0.05). Conclusion: The effective dose of CM extract 16 ml/kg BW had an effect on the cardiac of normal Wistar rats and diabetic models in the form of a decrease in the level of damage to degeneration, hypertrophy, and cardiac necrosis. Keywords: Cardiac, Channa micropeltes, Degeneration, Hypertrophy, Necrosis.